Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the equation [tex]\(\frac{11y - 2}{3} = y^2 + 2\)[/tex], we need to eliminate the fraction and solve for [tex]\(y\)[/tex]. Follow these steps:
1. Eliminate the fraction: Multiply both sides of the equation by 3 to clear the denominator.
[tex]\[ 3 \cdot \frac{11y - 2}{3} = 3 \cdot (y^2 + 2) \][/tex]
This simplifies to:
[tex]\[ 11y - 2 = 3y^2 + 6 \][/tex]
2. Rearrange the equation: Move all terms to one side to set the equation to zero.
[tex]\[ 11y - 2 - 3y^2 - 6 = 0 \][/tex]
Simplifying this, we get:
[tex]\[ -3y^2 + 11y - 8 = 0 \][/tex]
or equivalently:
[tex]\[ 3y^2 - 11y + 8 = 0 \][/tex]
3. Solve the quadratic equation: We use the quadratic formula [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex] where [tex]\( a = 3 \)[/tex], [tex]\( b = -11 \)[/tex], and [tex]\( c = 8 \)[/tex].
Calculate the discriminant:
[tex]\[ b^2 - 4ac = (-11)^2 - 4(3)(8) \][/tex]
[tex]\[ = 121 - 96 \][/tex]
[tex]\[ = 25 \][/tex]
Since the discriminant is positive, we have two distinct real solutions. Now, find the roots:
[tex]\[ y = \frac{-(-11) \pm \sqrt{25}}{2 \cdot 3} \][/tex]
[tex]\[ y = \frac{11 \pm 5}{6} \][/tex]
4. Calculate the roots:
[tex]\[ y_1 = \frac{11 + 5}{6} = \frac{16}{6} = \frac{8}{3} \][/tex]
[tex]\[ y_2 = \frac{11 - 5}{6} = \frac{6}{6} = 1 \][/tex]
Hence, the solutions to the equation [tex]\(\frac{11y - 2}{3} = y^2 + 2\)[/tex] are:
[tex]\[ y = 1 \quad \text{and} \quad y = \frac{8}{3} \][/tex]
1. Eliminate the fraction: Multiply both sides of the equation by 3 to clear the denominator.
[tex]\[ 3 \cdot \frac{11y - 2}{3} = 3 \cdot (y^2 + 2) \][/tex]
This simplifies to:
[tex]\[ 11y - 2 = 3y^2 + 6 \][/tex]
2. Rearrange the equation: Move all terms to one side to set the equation to zero.
[tex]\[ 11y - 2 - 3y^2 - 6 = 0 \][/tex]
Simplifying this, we get:
[tex]\[ -3y^2 + 11y - 8 = 0 \][/tex]
or equivalently:
[tex]\[ 3y^2 - 11y + 8 = 0 \][/tex]
3. Solve the quadratic equation: We use the quadratic formula [tex]\( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex] where [tex]\( a = 3 \)[/tex], [tex]\( b = -11 \)[/tex], and [tex]\( c = 8 \)[/tex].
Calculate the discriminant:
[tex]\[ b^2 - 4ac = (-11)^2 - 4(3)(8) \][/tex]
[tex]\[ = 121 - 96 \][/tex]
[tex]\[ = 25 \][/tex]
Since the discriminant is positive, we have two distinct real solutions. Now, find the roots:
[tex]\[ y = \frac{-(-11) \pm \sqrt{25}}{2 \cdot 3} \][/tex]
[tex]\[ y = \frac{11 \pm 5}{6} \][/tex]
4. Calculate the roots:
[tex]\[ y_1 = \frac{11 + 5}{6} = \frac{16}{6} = \frac{8}{3} \][/tex]
[tex]\[ y_2 = \frac{11 - 5}{6} = \frac{6}{6} = 1 \][/tex]
Hence, the solutions to the equation [tex]\(\frac{11y - 2}{3} = y^2 + 2\)[/tex] are:
[tex]\[ y = 1 \quad \text{and} \quad y = \frac{8}{3} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.